Building the Black Arts Movement : Hoyt Fuller and the Cultural Politics of the 1960s - Fenderson, Jonathan, 1980- (Book collections on Project MUSE., 2019)
"The project explores the history of the Black Arts Movement through the experience of activist and organizer, Hoyt W. Fuller (1923-1981). In the first book to document and analyze Fuller's profound influence on the movement, Fenderson attends to the paradox between Fuller's central role in the Movement and his marginal place in African-American historiography. The project rethinking both the Black Arts Movement and the broader Black cultural politics of the 1960s.Though focused on Fuller, the project is not simply a biographer; it is a series of historical vignettes covering different aspects of Fuller's cultural activism. As it chronicles Fuller's life, the book also address pivotal events and formative moments that grant insight into the ways the Black Arts Movement took shape at the local level; the ways artists shaped the Movement; how race, class, gender, sexuality, and corporate interests impacted the Movement; and, especially, how recovering Hoyt Fuller's work fundamentally alters our knowledge of the Black Arts Movement"--